Gestational trends in uterine artery pulsatility index and maternal blood pressure among pregnant women at 11-14 weeks to 34 weeks of gestation - Kuttiamu, Shahna; Balachandran Nair, M. R.; V., Binoj Varghese; Ramachandran, Lola (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pre-eclampsia (PE) and fetal growth restriction (FGR) are significant obstetric complications associated with impaired placental perfusion and adverse maternal and perinatal outcomes. Uterine artery pulsatility index (PI) and maternal mean arterial pressure (MAP) are established biophysical markers for predicting these conditions. However, longitudinal evaluation of these parameters in low-resource populations remains limited. This study aimed to assess gestational trends in uterine artery PI and MAP from 11–14 weeks to 34 weeks of gestation and their association with pregnancy outcomes. Methods: This prospective observational study was conducted over 18 months at a private medical college in Kerala, India. Pregnant women with singleton pregnancies at 11–14 weeks undergoing routine nuchal translucency scans were enrolled (n=128). Uterine artery Doppler and MAP were measured at 11–14, 20–24 and 30–34 weeks of gestation. PI was obtained using standard Doppler techniques and MAP was calculated from four arm measurements. Data were analyzed using paired-samples t tests, with p<0.05 considered statistically significant. Results: The mean uterine artery PI decreased progressively from 1.6±0.4 at 11–14 weeks to 1.1±0.4 at 20–24 weeks and further to 0.8±0.2 at 30–34 weeks (p<0.01). MAP remained relatively stable across gestation, within normal physiological ranges. The cohort was predominantly young (21–30 years, 60.9%) and primigravida (57.8%). Conclusions: Uterine artery PI shows a significant progressive decline with advancing gestation, reflecting normal uteroplacental adaptation, while MAP remains stable, indicating adequate cardiovascular adjustment. These findings support the utility of uterine artery Doppler and MAP monitoring in predicting adverse pregnancy outcomes and highlight the need for population-specific reference ranges.